Greater access to fast-food outlets is associated with poorer bone health in young children. Issue 3 (March 2016) - Vogel, C.; Parsons, C.; Godfrey, K.; Robinson, S.; Harvey, N.; Inskip, H.; Cooper, C.; Baird, J.
Abstract Summary A healthy diet positively influences childhood bone health, but how the food environment relates to bone development is unknown. Greater neighbourhood access to fast-food outlets was associated with lower bone mass among infants, while greater access to healthy speciality stores was associated with higher bone mass at 4 years. Introduction Identifying factors that contribute to optimal childhood bone development could help pinpoint strategies to improve long-term bone health. A healthy diet positively influences bone health from before birth and during childhood. This study addressed a gap in the literature by examining the relationship between residential neighbourhood food environment and bone mass in infants and children. Methods One thousand one hundred and seven children participating in the Southampton Women's Survey, UK, underwent measurement of bone mineral density (BMD) and bone mineral content (BMC) at birth and 4 and/or 6 years by dual-energy X-ray absorptiometry (DXA). Cross-sectional observational data describing food outlets within the boundary of each participant's neighbourhood were used to derive three measures of the food environment: the counts of fast-food outlets, healthy speciality stores and supermarkets. Results Neighbourhood exposure to fast-food outlets was associated with lower BMD in infancy (β  = −0.23 (z-score): 95 % CI −0.38, −0.08) and lower BMC after adjustment for bone area and confounding variables (β  = −0.17 (z-score): 95 % CI −0.32, −0.02). Increasing neighbourhood exposure to healthy speciality stores was associated with higher BMD at 4 and 6 years (β  = 0.16(z-score): 95 % CI 0.00, 0.32 andβ  = 0.13(z-score): 95 % CI −0.01, 0.26 respectively). The relationship with BMC after adjustment for bone area and confounding variables was statistically significant at 4 years, but not at 6 years. Conclusions The neighbourhood food environment that pregnant mothers and young children are exposed may affect bone development during early childhood. If confirmed in future studies, action to reduce access to fast-food outlets could have benefits for childhood development and long-term bone health.